Corruption and private participation infrastructure projects: The influence of vicarious experience and national animosity. (10th March 2020) - Jiménez, Alfredo; Bayraktar, Secil; Puche‐Regaliza, Julio César; Herrero, Alvaro
Abstract: This paper investigates the influence of vicarious experience and national animosity on the relationship between corruption and the performance of private participation infrastructure projects. Our analysis of 27, 264 projects in 114 countries from 1997 to 2013 shows that higher levels of corruption are associated with higher risk of project failure. We also find that this effect is weakened by the presence of other firms from the same industry, as firms may learn from other companies how to deal with corruption. In contrast, we find the effect is strengthened by the presence of other firms from different industries. This result is due to a lower applicability of knowledge and to an increase in national animosity and discrimination from local stakeholders. Résumé: Cet article porte sur l'influence que l'expérience par procuration et l'animosité nationale exercent sur la relation entre la corruption et la performance des projets d'infrastructure à participation privée. L'analyse de 27 264 projets dans 114 pays entre 1997 et 2013 révèle que des niveaux de corruption plus élevés sont associés à un risque plus élevé d'échec des projets. On constate également que cet effet est moindre lorsque d'autres entreprises du même secteur sont présentes, les entreprises pouvant apprendre d'autres entreprises comment faire face à la corruption. Mais il est renforcé lorsque des entreprises exerçant dans des secteurs différents sont présentes. Ce résultat est dû à une moindre applicabilité des connaissances et à une augmentation de l'animosité nationale et de la discrimination de la part des acteurs locaux.